Lectotypification of Pseudoglochidion anamalayanum Gamble and its taxonomic position under the genus Phyllanthus (Phyllanthaceae) - Pagare, Ravikiran S.; Naik, Sidhesh S.; Krishnan, Sellappan; Janarthanam, Malapati K. (Phytotaxa, 2016)
Pseudoglochidion anamalayanum Gamble (Phyllanthaceae), the only species of the genus is presently treated under Phyllanthus L. It is a narrow endemic of Western Ghats, India and is known from very few collections from Anamalais, Coimbatore district, Tamil Nadu. It has been assigned the threat status ‘Critically Endangered’ (CR) by World Conservation Monitoring Centre (1998). In the present study, its taxonomic position has been evaluated using molecular sequences of internal transcribed spacer (ITS) and chloroplast matK genes with a matrix of ITS and matK sequences of Phyllanthus. The results obtained from MEGA and Bayesian analyses have shown that Pseudoglochidion is nesting among the Phyllanthus species of subgenus Isocladus, which itself is polyphyletic. The morphological characters also support the taxonomic position of the species in Phyllanthus. A detailed description is provided and lectotype for the name Pseudoglochidion anamalayanum (≡ Phyllanthus anamalayanus) is designated here.